2009
DOI: 10.4103/0019-5545.44906
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between consanguinity and depression in a south Indian population

Abstract: A Pilot study was Carried out to study the association of consanguinity marriage with depression. It was observed that the consanguinity of marriage was associated with depression. The odds ratio was 5.66 (CI: 2.42-13.54). The age and sex had an association with depression. The age and sex adjusted odds ratio of consanguinity marriage was 7.66 (CI: 3.93-19.45) indicating that it is independently associated with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Likewise consanguinity seemed to be associated with depression only on bivariate testing. Consanguineous marriages are fairly prevalent in South India and clinical observations have reported a high prevalence of depression in such communities (61) which could be genetically driven (62). A major catastrophic event in the past 1 year was an important risk factor which was significantly associated with prenatal depression in this study; this is consistent with the study results reported by Leigh et al (63) and Shakeel et al (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise consanguinity seemed to be associated with depression only on bivariate testing. Consanguineous marriages are fairly prevalent in South India and clinical observations have reported a high prevalence of depression in such communities (61) which could be genetically driven (62). A major catastrophic event in the past 1 year was an important risk factor which was significantly associated with prenatal depression in this study; this is consistent with the study results reported by Leigh et al (63) and Shakeel et al (58).…”
Section: Discussionmentioning
confidence: 99%
“…Research done in other countries reportedly point toward an interconnection between obesity and depression (67, 68). The causal pathway could include inflammation (62), hormonal imbalance (69), or sleep disturbance (70).…”
Section: Discussionmentioning
confidence: 99%
“…Mansour (2009) finds genuine brain disorder causing violent temperament and behavior. Rao (2009) and Bener (2017) point out many other common mental diseases which are related to cousin marriages. These may be depression, anxiety and violent behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] In fact, genetic studies as such in respect of psychiatric disorders are very scarce in our country. We could find a pilot study to find the association of consanguinity and depression[ 6 ] and a pedigree study on the genetics of affective disorders. [ 7 ] There is a need to encourage genetics-based research in India to find out association of genetic factors with psychiatric disorders.…”
mentioning
confidence: 99%